Dexmedetomidine selectively suppresses dominant behaviour in aggressive and sociable mice - Votava, Martin; Hess, Ladislav; Slíva, Jirí; Krsiak, Miloslav; Agová, Viktoria (European journal of pharmacology, 2005)
Dexmedetomidine is a highly specific alpha2-adrenoreceptor agonist, which is now clinically used to induce sedation in patients in the intensive care units. Behavioural effects of dexmedetomidine have been little studied so far. The drug was reported to reduce behaviour such as locomotion or measures of anxiety or aggression in animals. The aim of the present study was to ascertain whether dexmedetomidine inhibits behaviour uniformly or with respect to particular stimuli or situations. Therefore, behavioural effects of dexmedetomidine were studied in the social conflict test in male mice (after three weeks of individual housing), which provides a wide spectrum of behavioural activities in two types of animals (aggressive and sociable mice) as well as in the activity cage. Dexmedetomidine (5-40 microg/kg i.p.) decreased locomotion in the activity cage and this effect was fully antagonized by atipamezole, a selective alpha2-adrenereceptor antagonist. However, dexmedetomidine did not reduce locomotion during social conflict. The only significant effects during social conflict were a selective and dose-dependent antiaggressive effect in aggressive mice and a selective reduction of social investigation ('sociability') in sociable mice. Thus, dexmedetomidine appears to inhibit predominantly dominant behaviour evoked by biologically important stimuli. The ability of dexmedetomidine to reduce aggression might be utilized for treatment of aggressive states. Sedation caused by dexmedetomidine can be easily disrupted and thus the drug may have an advantage over benzodiazepines or neuroleptics, which are used in this indication.
Keywords: Imidazoles; Behavior, Animal; Social Behavior; Analysis of Variance; Male; alfa-2-adrenergní receptory; imidazoly; vztah mezi dávkou a účinkem léčiva; dexmedetomidin; mužské pohlaví; alfa blokátory; Adrenergic alpha-Agonists; Mice, Inbred ICR; agonisté adrenergních alfa-receptorů; Conflict, Psychological; Adrenergic alpha-Antagonists; Animals; analýza rozptylu; zvířata; pohybová aktivita; Receptors, Adrenergic, alpha-2; Motor Activity; myši; myši inbrední ICR; chování zvířat; sociální chování; konflikt (psychologie); Mice; Aggression; agrese; Dexmedetomidine; Dose-Response Relationship, Drug